Karakteristik Bakso Daging Kuda yang Diberi Tepung Tapioka (Manihot Esculenta) dan STPP (Sodium Tripoliphoapat) Terhadap Kualitas Fisik dan Organoleptik: Characteristics of Horse Meat Meatballs Given Tapioca Flour (Manihot Esculenta) and STPP (Sodium Tripolyphoapat) on Physical and Organoleptic Quality (Jurnal Riset Agribisnis dan Peternakan, 2024)
Horse meat has a tough texture. To be able to consume it deliciously, it is necessary to have processing that can reduce the toughness of the meat by making horse meat meatballs. The aim of this research was to determine the effect of tapioca flour and STPP (Sodium Tripolyphosphate) levels on the physical and organoleptic quality of horse meat meatballs. The research was conducted at the Integrated Laboratory of Muhammadiyah University, Purworejo. The ingredients used are 10 kg of horse meat, tapioca flour, STTP (Sodium Tripolyphosphate). The design used was a Completely Randomized Design (CRD) Factorial Pattern with 4 treatments, 3 replications, 3 factorials. The addition of tapioca flour did not have a significant effect on the organoleptic properties and pH of horse meat meatballs, but had a significant effect on the tenderness (physical properties) of horse meat meatballs. The addition of STTP to horse meat meatballs has no significant effect on the organoleptic properties and tenderness (physical properties) of horse meat meatballs, but has a significant effect on the pH of horse meat meatballs
Keywords: Horse meat; Meatballs; Manihot Esculenta; Sodium Tripolyphoapat